PERAN LEMBAGA PENJAMIN SIMPANAN TERHADAP SALDO UANG ELEKTRONIK PADA DOMPET ELEKTRONIK DANA - Yuda Anrova; Albert Sembiring (LPPM Universitas Bina Bangsa, 2022)
DANA is a technology for electronic wallet or e-wallet that is used for transactions without cash or cards but only with a user's start. That ease and effectiveness led to the high consumption of DANA. But lately electronic wallet users have concerns over the balance on their electronic wallets. Indonesian have Institution Lembaga Penjamin Simpanan (LPS) is regulated number 24 of 2004, it provides security and gives its customers confidence in existing systems and institutions. It is still a matter of whether LPS played a part in the transaction. The research aims to see the extent of LPS 'role in transactions in DANA applications. By using descriptive research methods of anaitis by using secondary data of legislation, previous research, and literature. The study shows that LPS has no role in the protection of public money that is kept in the application of DANA because legal regulations do not permit it. The LPS also have no intervention function in policy or financial transaction activities in the fund in DANA